A new complimentary web‐based tool for manual analysis of microcirculation videos: Validation of the Capillary Mapper against the current gold standard AVA 3.2. (8th October 2018) - Hessler, Michael; Arnemann, Philip‐Helge; Zamit, Frédéric; Seidel, Laura; Kampmeier, Tim‐Gerald; Kathöfer, Ulrich; Morelli, Andrea; Ince, Can; Rehberg, Sebastian W.; Ertmer, Christian
Abstract: Objective: The aim of the current study was to compare a newly developed web‐based freely accessible software program for manual analysis of the microcirculation, the Capillary Mapper (CM), with AVA 3.2 software (AVA; MicroVision Medical B.V., Amsterdam, The Netherlands), which is the current gold standard for analysis of microcirculation videos. Methods: A web‐based software program was developed, which enables manual analysis of videos of the microcirculation to be carried out according to recommendations of the 2018 consensus conference. A set of 50 high quality microcirculation videos was analyzed with AVA and CM with respect to total vessel density, perfused vessel density, proportion of perfused vessels, and the microvascular flow index. Results: Comparison of the mean values derived from manual analysis with CM and AVA revealed no significant differences in microcirculatory variables. Analysis according to Bland and Altman revealed an acceptable bias between manual analysis with the CM and AVA for all variables tested with sufficient limits of agreement. The analysis of intraclass correlation showed "excellent" agreement for all microcirculatory variables analyzed. Conclusions: The newly developed CM was successfully validated for manual analyses of microcirculation videos against the current gold standard, the software AVA 3.2.